Opini Publik Terhadap Kebijakan Pemerintah Mengenai Pemusnahan Pakaian Bekas Impor: Analisis Isi Kuantitatif Kolom Komentar Instagram - Maulidia, Shafira Sekar; Saragih, Nurhayani (Jurnal Mahardika Adiwidia, 2024)
The goal of this study is to examine the public's positive, negative, and neutral reactions to the March 27, 2023, post "Minister of Trade Will Destroy Imported Used Clothes" on Instagram @jktinfo. This study employs positivism as a paradigm and quantitative content analysis as a research method. We analyze the content of messages or texts per comment and conceptualize it using public opinion as the unit of analysis. This study had a population of 2,257, and the sample included 339 comments. Data collection techniques rely on random sampling. Additionally, intercoders with Hostly formulas test the data for validity and reliability.The results showed positive opinions of 63 (19 persen of comments) that supported the policies of the Minister of Trade, negative opinion categories of 263 (77 persen of comments) that rejected and did not support, and neutral opinions that received frequency results of 13 (4 persen of comments) that were impartial to any party. The study identified five sub-dimensions of language style: irony, cynicism, sarcasm, satire, and innuendo. Cynicism in negative opinions emerged as the most popular sub-dimension of language style, garnering up to 92 comments, indicating the public's rejection and disapproval of the Ministry of Trade's policy to destroy imported used clothes.